Angiopoietin 2 levels decrease after HCV-cure and reflect the evolution of portal hypertension. Issue 9 (September 2022) - Bauer, David; Kozbial, Karin; Schwabl, Philipp; Chromy, David; Simbrunner, Benedikt; Stättermayer, Albert F.; Pinter, Matthias; Steindl-Munda, Petra; Trauner, Michael; Ferenci, Peter; Reiberger, Thomas; Mandorfer, Mattias
Abstract: Background: Portal hypertension (PH) does not resolve in a considerable proportion of patients who achieved HCV-cure. Aims: To investigate (i) whether HCV-cure impacts cytokines that orchestrate angiogenesis (i.e., Ang1/Ang2/VEGF) and fibrogenesis (i.e., PDGF/TGF-β) and (ii) whether their changes reflect PH-evolution and its complications. Methods: We measured plasma levels of cytokines and von Willebrand factor (VWF) and assessed hepatic venous pressure gradient (HVPG) before/after HCV-cure in 66 patients with pre-treatment PH and 23 patients without advanced disease, who served as controls. Results: Following HCV-cure, we observed a decrease in Ang2/TGF-β, but no changes in the other cytokines. The differences in circulating cytokine profiles in PH patients persisted after removing the primary etiological factor. Patients with pre-treatment HVPG≥10 mmHg with HVPG-reduction≥10% had a more pronounced relative decrease in Ang2. Finally, post-treatment Ang2 predicted FU-HVPG≥16 mmHg/decompensation with AUROC-values of 0.804/0.835. Conclusions: HCV-cure decreases circulating Ang2 – a mediator/indicator of dysangiogenesis/endothelial dysfunction, as well as TGF-β – a profibrogenic cytokine. The dynamics of Ang2 mirrored those of PH, rendering FU-Ang2 a non-invasive test for pronounced PH at FU that also predicts hepatic decompensation. The pathophysiological significance of the persistently altered cytokine levels for mechanisms that hinder the PH-regression warrants further study.